High operator and hospital volume are associated with a decreased risk of death and stroke after carotid revascularization: a systematic review and meta-analysis - Poorthuis, M; Brand, E; Halliday, A; Bots, M; Bulbulia, R; De Borst, G (Lippincott, Williams and Wilkins, 2019)
OBJECTIVE: To examine the association between operator or hospital volume and procedural outcomes of carotid revascularization. BACKGROUND: Operator and hospital volume have been proposed as determinants of outcome after carotid endarterectomy (CEA) or carotid artery stenting (CAS). The magnitude and clinical relevance of this relationship are debated. METHODS: We systematically searched PubMed and EMBASE until August 21, 2017. The primary outcome was procedural (30 days, in-hospital, or perioperative) death or stroke. Obtained or estimated risk estimates were pooled with a generic inverse variance random-effects model. RESULTS: We included 87 studies. A decreased risk of death or stroke following CEA was found for high compared to low operator volume with a pooled adjusted odds ratio (OR) of 0.50 (95% confidence interval [CI] 0.28-0.87; 3 cohorts), and a pooled unadjusted relative risk (RR) of 0.59 (95% CI 0.42-0.83; 9 cohorts); for high compared to low hospital volume with a pooled adjusted OR of 0.62 (95% CI 0.42-0.90; 5 cohorts), and a pooled unadjusted RR of 0.68 (95% CI 0.51-0.92; 9 cohorts). A decreased risk of death or stroke after CAS was found for high compared to low operator volume with an adjusted OR of 0.43 (95% CI 0.20-0.95; 1 cohort), and an unadjusted RR of 0.50 (95% CI 0.32-0.79; 1 cohort); for high compared to low hospital volume with an adjusted OR of 0.46 (95% CI 0.26-0.80; 1 cohort), and no significant decreased risk in a pooled unadjusted RR of 0.72 (95% CI 0.49-1.06; 2 cohorts). CONCLUSIONS: We found a decreased risk of procedural death and stroke after CEA and CAS for high operator and high hospital volume, indicating that aiming for a high volume may help to reduce procedural complications. REGISTRATION: This systematic review has been registered in the international prospective registry of systematic reviews (PROSPERO): CRD42017051491.